2019
DOI: 10.1242/jeb.202986
|View full text |Cite
|
Sign up to set email alerts
|

What goes up must come down - biomechanical impact analysis of falling locusts

Abstract: Many insects are able to precisely control their jumping movements. Once in the air, the properties of the actual landing site, however, are almost impossible to predict. Falling insects thus have to cope with the situation at impact. In particular, for insects jumping to escape predators, a controlled landing movement appears to be a major evolutionary advantage. A quick recovery into an upright and stable body posture minimizes the time to prepare for the next escape jump. In this study, we used high-speed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…To land securely, SLF nymphs need to quickly dissipate kinetic energy via a combination of air drag, work of adhesion, surface friction, and deformation of the body and substrate. High-speed video revealed that the majority of SLF nymphs accomplished this in large measure by bouncing after impact when landing, resulting in energy losses similar to the values reported for head-on collisions by crashlanding locusts (76%) (Reichel, Labisch and Dirks, 2019) and by running cockroaches hitting walls (95%) (Jayaram et al, 2018). Just as adhesive foot pads were noted to influence landing mechanics for falling pea aphids and locusts (Ribak et al, 2013;Reichel, Labisch and Dirks, 2019), SLF nymphs in this study also made use of adhesion to paper and leaves to reorient and come to rest after bouncing.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…To land securely, SLF nymphs need to quickly dissipate kinetic energy via a combination of air drag, work of adhesion, surface friction, and deformation of the body and substrate. High-speed video revealed that the majority of SLF nymphs accomplished this in large measure by bouncing after impact when landing, resulting in energy losses similar to the values reported for head-on collisions by crashlanding locusts (76%) (Reichel, Labisch and Dirks, 2019) and by running cockroaches hitting walls (95%) (Jayaram et al, 2018). Just as adhesive foot pads were noted to influence landing mechanics for falling pea aphids and locusts (Ribak et al, 2013;Reichel, Labisch and Dirks, 2019), SLF nymphs in this study also made use of adhesion to paper and leaves to reorient and come to rest after bouncing.…”
Section: Discussionsupporting
confidence: 53%
“…This interpretation is supported by our finding that, in spite of impacting the surface with similar speeds and orientations, live SLF nymphs finally landed upright significantly more often than dead specimens, even those with legs spread. To understand this phenomenon, we first note that almost all live and dead specimens bounced after impact so as to dissipate most of their pre-impact energy (> 97% for live and >94% for dead specimens), similar to values reported for crash-landing locusts (76%) (24) and cockroaches running into walls (95%) (32). This is important because nymphs benefit from dissipating most of their kinetic energy quickly in order to land securely, while retaining enough kinetic energy to surmount potential energy barriers that can prevent the reorientations required for righting.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Small size permits a simple mechanically mediated solution for landing—a head-on collision where kinetic energy is absorbed 34 . Numerous small flying, running, and jumping animals such as bees 41 , fruit flies 42 , locusts 43 , and cockroaches 34 , 44 undergo frequent collisions and head-on crash landings. Considering the effect of size, a small lizard of ~2 g might be able to crash-land into a tree without injury, whereas a ~2 kg flying lemur might experience injury and plastic deformation in the form of damage to tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Their results show that the insects use a gliding mechanism to change the free-falling trajectory and achieve controlled landing back on the trees without hitting the ground [48][49][50]. The velocities of these beetles are more than twice the values reported in falling ants and locusts [48][49][50][51]. Also, the average body mass of these beetles is relatively much higher when compared to that of the ants and the spiders used in the experiments.…”
Section: Puncture and Wear Resistancementioning
confidence: 90%